From empire to humanity: the American Revolution and the origins of humanitarianism - Moniz, Amanda B. (Oxford University Press, 2016)
"From Empire to Humanity tells the story of a generation of American and British activists who transformed humanitarianism as they adjusted to becoming foreigners to each other in the wake of the American Revolution. In the decades before the Revolution, Americans and Britons shared an imperial approach to charitable activity. They worked together in benevolent ventures designed to strengthen the British empire, and ordinary men and women donated to help faraway members of the British community. Raised and educated in this world of connections, future activists from the British Isles, North America, and the West Indies developed expansive outlooks and transatlantic ties. For budding doctors--including Philadelphia's Benjamin Rush, Caribbean-born Londoner John Coakley Lettsom, and John Crawford, whose life took him from Ireland to India, Barbados, South America, and, finally, Baltimore--this was especially true. American independence put an end to their common imperial humanitarianism, but not their friendships, their far-reaching visions, or their belief in philanthropy as a tool of statecraft. In the postwar years, with doctor-activists at the forefront, Americans and Britons collaborated in the anti-drowning cause and other medical philanthropy, antislavery movements, prison reform, and more. No longer members of the same polity, the erstwhile compatriots adopted a universal approach to their beneficence as they reimagined their bonds with people who were now foreigners. Universal benevolence could also be a source of tension. With the new wars at the end of the century, activists' optimistic cosmopolitanism waned, even as their practices endured. Making the care of suffering strangers routine, they laid the groundwork for later generations' global undertakings "--